Pitfalls of NMDA Receptor Modulation by Neuroactive Steroids. The Effect of Positive and Negative Modulation of NMDA Receptors in an Animal Model of Schizophrenia - Holubova, Kristina; Chvojkova, Marketa; Hrcka Krausova, Barbora; Vyklicky, Vojtech; Kudova, Eva; Chodounska, Hana; Vyklicky, Ladislav; Vales, Karel (Biomolecules, 2021)
Evidence from clinical and preclinical studies implicates dysfunction of N-methyl-D-aspartate receptors (NMDARs) in schizophrenia progression and symptoms. We investigated the antipsychotic effect of two neuroactive steroids in an animal model of schizophrenia induced by systemic application of MK-801. The neuroactive steroids differ in their mechanism of action at NMDARs. MS-249 is positive, while PA-Glu is a negative allosteric NMDAR modulator. We hypothesized that the positive NMDA receptor modulator would attenuate deficits caused by MK-801 co-application more effectively than PA-Glu. The rats were tested in a battery of tests assessing spontaneous locomotion, anxiety and cognition. Contrary to our expectations, PA-Glu exhibited a superior antipsychotic effect to MS-249. The performance of MS-249-treated rats in cognitive tests differed depending on the level of stress the rats were exposed to during test sessions. In particular, with the increasing severity of stress exposure, the performance of animals worsened. Our results demonstrate that enhancement of NMDAR function may result in unspecific behavioral responses. Positive NMDAR modulation can influence other neurobiological processes besides memory formation, such as anxiety and response to stress.
Keywords: schizophrenia; lidé; potkani Long-Evans; Schizophrenia; Dizocilpine Maleate; krysa rodu Rattus; antipsychotika; Elevated Plus Maze Test; dizocilpinmaleát; anxiety; MK-801; úleková reakce; Rats, Long-Evans; chování zvířat; Humans; Antipsychotic Agents; potkani Wistar; stress; Steroids; receptory N-methyl-D-aspartátu; pregnenolon; Disease Models, Animal; Rats, Wistar; Reflex, Startle; HEK293 Cells; HEK293 buňky; mužské pohlaví; zvířata; Pregnenolone; steroidy; schizofrenie; Rats; Receptors, N-Methyl-D-Aspartate; Animals; cognition; Male; modely nemocí na zvířatech; test vyvýšeného křížového bludiště; Bridged Bicyclo Compounds, Heterocyclic; Behavior, Animal; neurosteroids; bicyklické sloučeniny heterocyklické